HbA1c Levels in Diabetes Mellitus Screening and Diagnosis - Ima Rahmawati; Emyk Windartik (Kirana Publisher (KNPub), 2023)
Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar due to decreased insulin secretion by pancreatic beta cells and impaired insulin function (insulin resistance). By measuring glycohemoglobin (HbA1c) you can find out what percentage of the red blood cell dye (hemoglobin) contains sugar. To analyze HbA1c levels in screening and early diagnosis of diabetes mellitus. Observational descriptive research design. The population in this study were all type 2 DM sufferers at Bangil Pasuruan Regional Hospital, totaling 79 respondents. The sample consisted of 47 respondents taken using a purposive sampling technique. The research instrument was an examination of HbA1c levels and an observation sheet. With controlled HbA1c levels, all of them have a normal BMI, eat a regular diet regularly take insulin medication, and adopt more regular exercise habits. Meanwhile, respondents with uncontrolled HbA1c had a BMI of underweight, normal, overweight, and most did not exercise regularly and did not regularly take antidiabetic drugs.